Isolation of some microorganisms from Iraqi patients with chronic maxillary sinusitis. - Zeiny, Sarmad M.; Al-Salloum, Suhaila M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Maxillary sinusitis is one of the most common infections of humans. Sinusitis can be defined as an inflammation of the membrane lining of any sinus, especially one of the paranasal sinuses. Objective: To determine the causative microorganisms of chronic maxillary sinusitis. Patients: Forty five chronic sinusitis patients were involved in the present study. Methods: Sampling method were sinus specimens (aspiration or injection aspiration). Results: Haemophilus species, Streptococcus pneumoniae (S.pneumoniae) and Moraxella catarrhalis (M.catarrhalis) were the most frequent isolates; in addition Penicillium and Cladosporium species were isolated from some chronic sinusitis patients. Conclusion: Chronic sinusitis could be caused by either bacterial species or by fungal species; most bacterial isolates were Haemophilus species followed by S.pneumoniae and M.catarrhalis. The incidences of chronic sinusitis were more at patients age (20-29 years) old groups.